Acceptance and Commitment Therapy in the Treatment of Alcohol Use Disorder and Comorbid Affective Disorder: A Pilot Matched Control Trial. Issue 6 (November 2015) - Thekiso, Thekiso B.; Murphy, Philip; Milnes, Jennie; Lambe, Kathryn; Curtin, Aisling; Farren, Conor K.
Abstract: This study examined whether acceptance and commitment therapy (ACT) enhances treatment as usual (TAU) in improving treatment outcomes in patients with alcohol use disorder (AUD) and comorbid affective disorder. Fifty-two participants were included in the study, of whom 26 were patients with AUD and either depression or bipolar disorder treated with ACT group therapy in parallel with TAU (inpatient integrated treatment) and 26 were matched controls who had received TAU alone. Drinking and craving outcomes were total alcohol abstinence, cumulative abstinence duration (CAD) and Obsessive Compulsive Drinking Scale (OCDS) scores at 3 and 6 months postintervention. Affective and anxiety outcomes were Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI) and Young Mania Rating Scale (YMRS) scores at these follow-ups. Baseline demographic and clinical characteristics were similar in both groups. Retention rates were high: 100% of the ACT group were followed up at 3 and 6 months; 92.3% and 84.6% of the TAU alone group were followed up at 3 and 6 months, respectively. Patients in the ACT group reported significantly higher CAD at 3 and 6 months, significantly lower BDI and BAI scores at 3 and 6 months, and significantly lower OCDS scores at 3 months, than those who received only TAU. No other significant differences in treatment outcomes were found between the groups. ACT provides added benefit to TAU in improving drinking, craving, depression and anxiety outcomes in patients with AUD and comorbid affective disorder. Most treatment improvements were sustained over a 6-month follow-up period. Highlights: Examined acceptance and commitment therapy (ACT) for alcohol use disorder (AUD) and comorbid affective disorder Compared ACT plus treatment as usual (TAU) to TAU alone on treatment outcomes ACT enhances TAU in improving drinking, craving, depression and anxiety outcomes Most treatment improvements were sustained over a 6-month follow-up period